Vibrational energy harvesting using smart materials - Ang, Sabrina Shu Qin (2010)
Vibration-based energy harvesting has rapidly advanced through the years, creating greater possibility of continuous and battery free power supply using the wireless electronics. In the recent years, smart materials have established their useful applications in harvesting of vibrational energy in the form of sensors and actuators. This is due to their intrusive nature and unique electro- mechanical coupling effect.